Magnetic Studies of Iron Oxide Nanoparticles Encapsulated within Nanostructured Silicon. (18th September 2015) - Granitzer, Petra; Rumpf, Klemens; Gonzalez-Rodriguez, Roberto; Coffer, Jeffery; Poelt, Peter; Reissner, Michael
Abstract : In the frame of this work the structural and magnetic characterization of encapsulated iron oxide nanoparticles within a nanostructured silicon host is discussed. Two approaches are depicted, one to infiltrate readily synthesized Fe3 O4 particles into the pores and second to grow iron oxide inside the pores out of an ethanolic iron salt solution. Beside the particle size dependent investigations, a key point of the presentation is the optimization of the system with respect to the desired magnetic properties (magnetic moment as high as possible, blocking temperature below room temperature) which are controlled by the filling parameters as well as by the morphology of the host. All investigated composite systems exhibit a blocking temperature far below room temperature and due to the fact that all utilized materials are biocompatible the presented systems are promising for using as magnetic vehicle in biomedicine.